Microplastics in Pelagic and Demersal Fishes of Pantai Baron, Yogyakarta, Indonesia - Suwartiningsih, Nurul; Setyowati, Indri; Astuti, Resa (Jurnal Biodjati, 2020)
Yogyakarta is the second-largest producer of plastic waste in Indonesia. Plastic waste in the waters can be degraded into microplastics that can enter the body of a fish. This study aimed to determine the presence of microplastics in the digestive tract of several species of fish in Pantai Baron, Yogyakarta, Indonesia. This research was an exploratory research conducted in April-September 2019 at Pantai Baron, Yogyakarta. Two species of each pelagic and demersal fish samples were taken by buying fish caught by fishermen. The digestive tract of fish was extracted with 10% KOH, filtered, then visual identification. Microplastic types were estimated by FT-IR spectrometry. The amount of microplastic of all fishes was done by Kruskal-Wallis test while the number of microplastics of the two categories of fish was compared with the Mann-Whitney test. A correlation analysis was carried out between the length of the fish, the weight of the digestive tract, and the number of microplastics found. Microplastic shape, color, size, and type data were analyzed descriptively. A total of 78 of the 80 (97.50%) fish from four species studied contained microplastics with a total number as many as 3,651 (mean 45.60 ± 44.31 microplastic/individual). About 100% of pelagic fish samples contained microplastics, while only 95% of demersal fish samples contained microplastics. Mann-Whitney test results showed the number of microplastic/ individual was significantly different between pelagic and demersal fish (p <0.05). The most dominant shape of microplastic was fiber (53.14%), film (36.97%) and fragments (9.89%). The type of polymers detected was polyamide. The results showed that pelagic fish swallowed more microplastics than demersal fish did because of the microplastic nature that is lightweight and floats. Microplastic characteristic data can be used to estimate the main source of microplastic pollution in Pantai Baron so it can be managed appropriately.